Estudo da hepatite B oculta em doadores de sangue de Vitória, Espírito Santo - Tovar, Thais Tristão (2012)
Occult hepatitis B (OHB) is defined as the presence of low levels of HBV DNA in the liver or serum of individuals testing hepatitis B surface antigen (HBsAg) negative. In most cases of OHB, sera are positive for hepatitis B core antibody. The literature contains quite a few studies on the prevalence of OHB in Brazil, as well as in the worldwide population. Such reports, often controversial, demonstrate that the OHB prevalence varies among healthy individuals or patients with diseases unrelated to the liver and patients with chronic liver disease. Despite efforts, it is necessary a better understanding of: the reasons for the persistence of low levels of HBV-DNA in the absence of detectable HBsAg, the potential risk of OHB transmission and its role in the progression and aggravation of some liver diseases. Therefore, it is interesting to know the prevalence of OHB indifferent population samples which allows de monitoring of carriers of the occult infection, followed prospectively in order to try to surprise the possible effects of the presence of low levels of HBV-DNA in these individuals. In this study we investigated the presence of Occult Hepatitis B in peripheral blood obtained from 520 healthy donors of Vitoria, Espirito Santo, with the aim of guiding policies to include or not the sensitive HBV-DNA nucleic acid amplification technique (NAT) screening in blood donations with a detection limit of 54UI/mL. In order to enable the molecular detection we had also developed a method that screens plasma samples in pools which is capable of detecting the presence of HBV in the ratio of 1:40.Through the technique of nested-PCR we found that 0,2% (1/520) had occult HBV in serum samples. Despite the low prevalence of OHB detected in the study, a considerable number of patients with occult HBV infection may not have been detected if the blood units were only tested for serological markers of HBV infection. So it is important to know the prevalence of OHB in one or more additional population groups, in order to follow up carriers of occult infection prospectively to determine possible effects of the presence of HBV-DNA in low concentrations in these individuals